2017
DOI: 10.15195/v4.a23
|View full text |Cite
|
Sign up to set email alerts
|

The Entrepreneur's Network and Firm Performance

Abstract: Diverse organizational forms coexist in China's market economy, adapting and evolving in intensely competitive production markets. We examine the networks of founding chief executive officers of private manufacturing firms in seven cities of the Yangzi River Delta region in China. Through sequence analysis of ties that entrepreneurs relied on for help in the founding and critical events of their businesses, we identify three discrete forms of network governance: traditional kin-based, hybrid nonkin, and ration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…They presented a model for evaluating the performance of the firms' SC network. Nee et al (2017) studied the relationship between the network and firm performance and found that network ties are linked with firm assets and equity, and enhance the SC performance. They critically examined the nodes and ties that matter in the relationship between the network and firm performance.…”
Section: Smes' Credit Qualitymentioning
confidence: 99%
“…They presented a model for evaluating the performance of the firms' SC network. Nee et al (2017) studied the relationship between the network and firm performance and found that network ties are linked with firm assets and equity, and enhance the SC performance. They critically examined the nodes and ties that matter in the relationship between the network and firm performance.…”
Section: Smes' Credit Qualitymentioning
confidence: 99%
“…More and more studies of corporate finance have been undertaken from a social network perspective. Numerous authors have assembled various types of social networks, such as board network (Larcker, So, & Wang, 2013), CEO network (El-Khatib, Fogel, & Jandik, 2015), venture capital network (Hochberg, Ljungqvist, & Lu, 2007) and so on, and they have provided empirical evidence of these networks' effects on corporate governance (Chen, Wang, & Lin, 2014;Nee, Liu, & DellaPosta, 2017;Kim, 2017). Supply networks share common features with these networks in terms of information acquisition and reciprocal cooperation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, a firm's embedded social networks have a substantial influence on its operating conditions and financial decisions. Relevant studies indicate that having a favorable position in a social network provides a firm with opportunities to improve innovation ability (Bell, 2005;Whittington, Owensmith, & Powell, 2009;De Prato & Nepelski, 2014), achieve higher return on investment (Hochberg, Ljungqvist, & Lu, 2007;Larcker, So, & Wang, 2013;El-Khatib, Fogel, & Jandik, 2015), and secure financing at a lower cost (Chuluun, Prevost, & Puthenpurackal, 2014;Engelberg, Gao, & Parsons, 2012), which all help the firm to enhance overall performance (Zaheer & Bell, 2005;Kim, 2017;Nee, Liu, & DellaPosta, 2017;Carnovale, Rogers, & Yeniyurt, 2019). As a vital social network where firms are embedded, the supply network exerts a pivotal influence on corporate economic behavior and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have shown that several factors can affect the performance of MSMEs, including capital deepening and human capital (Badriah et al, 2019) and social capital (Prakasa, 2018;Nee et al, 2017;Hoq et al, 2017;Dai et al, 2015;Felício et al, 2014). Bourdieu (1980) in Kuncoro (2010) defines social capital as an aggregate of actual and potential resources that are bound to create networking to institutionalize mutually beneficial friendly relations.…”
Section: Introductionmentioning
confidence: 99%